Analisis SWOT Kesiapan Pembelajaran Tatap Muka Terbatas pada Era New Normal di Kampus Undaris - Kurnianto, Bagas (Faculty of Teacher Training and Education of Undaris, 2022)
The Covid-19 pandemic has changed all sectors of human life, including the world of education and teaching. The transformation of teaching experienced massive changes, ranging from teaching styles, learning models to learning evaluation. However, the relaxation of social access restrictions in early 2022 provides an opportunity for face-to-face learning to be held. The purpose of this study was to analyze the readiness of face-to-face learning in the new normal era with a SWOT matrix analysis for Undaris students. This research method is qualitative to formulate the readiness needed in carrying out limited face-to-face learning. The subjects of this study were all Undaris students. Meanwhile, data collection uses a questionnaire with the help of the google form application. The results obtained four formulations from the SWOT analysis, namely the Strength–Opportunities (SO) strategy, Weaknesses–Opportunities (WO), Strength–Threats (ST), and Weaknesses–Threat (WT) strategies, among others, improving the quality and standards of learning, restoring commitment students, evaluation of new building construction activities, and adjustment of lecture halls. The conclusion in this study is that the SWOT analysis in limited face-to-face learning can be used as a reference and input in improving learning standards for lecturers, students, and institutions so that the quality of learning at Undaris is maintained and optimal.Keywords: SWOT analysis, face-to-face learning, new normal